Clostridioides difficile infection in Saudi Arabia: Prevalence, risk factors, and outcomes in a tertiary hospital setting - Abdullah M. Aldhaif; Mohammed A. Al-Garni; Ahmed A. Muyidi; Mohammed H. Makkawi (PLoS ONE, 2025)
Background Clostridioides difficile infection (CDI) remains a major healthcare-associated infection with limited contemporary data from Saudi Arabia. This study evaluated CDI prevalence, risk factors, recurrence predictors, and treatment patterns in hospitalized patients at a tertiary teaching hospital. Methods Retrospective analysis of 1,054 hospitalized patients screened between March 2023 and February 2024. CDI was confirmed by positive toxin assay and/or nucleic acid amplification test (NAAT). Demographic, clinical, antibiotic, acid-suppressant, and treatment data were collected. Bivariate associations and multivariable logistic regression were used to identify predictors of recurrence. Results CDI prevalence was 10.8% (114/1,054). Median age was 37 years (IQR 51.25); 32.5% had malignancy. Antibiotic exposure preceded CDI in 59.6% (meropenem 24.7%, ceftriaxone 16.5% of courses), and acid suppressants were used in 57.0% (omeprazole 92.3%). Recurrence occurred in 11.4% (13/114). On bivariate analysis, acid-suppressant use was significantly associated with recurrence ( p = 0.041). In multivariable logistic regression, only metronidazole plus vancomycin combination therapy independently predicted recurrence (OR 11.29, 95% CI 1.13–112.42, p = 0.039). Trends were observed for malignancy (OR 2.94, p = 0.112) and acid-suppressant use (OR 1.85, p = 0.440), limited by the small number of recurrent events. Metronidazole monotherapy dominated treatment (64.8%). Conclusion CDI prevalence reached 10.8% with an 11.4% recurrence rate. Acid-suppressant exposure and combination therapy were key recurrence signals, while metronidazole remains overused despite international guideline shifts. Enhanced antibiotic and acid-suppressant stewardship, alongside improved access to guideline-recommended therapies, are critical to reducing CDI burden in Saudi tertiary hospitals.